การพัฒนาผลิตภัณฑ์สบู่สมุนไพรจากตาลโตนดของกลุ่มท่องเที่ยวเชิงอนุรักษ์ อำเภอสทิงพระ จังหวัดสงขลา - ชูสงค์ จารุวรรณ; ศิริรักษ์ ไพฑูรย์ (RMUTSB ACADEMIC JOURNAL, 2014)
การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อพัฒนายกระดับผลิตภัณฑ์และพัฒนาสบสู่ มุนไพรจากตาลโตนดกลุ่มท่องเที่ยวเชิงอนุรักษ์ อำเภอสทิงพระ จังหวัดสงขลาให้มีคุณภาพและมาตรฐาน รวมทั้งส่งเสริมการจัดการตลาดของกลุ่ม โดยการใช้รูปแบบการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม ผลการวิจัย พบว่า 1) ในการพัฒนาผลิตภัณฑ์ทำให้กลุ่มมีศักยภาพในการยกระดับมาตรฐานผลิตภัณฑ์ในด้านคุณภาพของผลิตภัณฑ์ กระบวนการผลิต รูปแบบบรรจุภัณฑ์ ระบบบัญชี และการตลาด 2) ผลการพัฒนาคุณภาพผลิตภัณฑ์ด้านเวชสำอางของสบู่สมุนไพรตาลโตนด ในการทดสอบฤทธิ์ Anti-microbial activity พบว่าสบสู่ มุนไพรตาลโตนดมีฤทธิ์ต้านเชื้อรา 3) ผลการพัฒนากระบวนการผลิตและผลการพัฒนาด้านบรรจุภัณฑ์แบบมีส่วนร่วม เน้นความเป็นเอกลักษณ์ของท้องถิ่นเพื่อสอดรับกับวิถีชีวิตของชุมชนได้อย่างมีประสิทธิภาพ Development of the Herbal Soap Product from the Palmyrah Fruit of the Conservation Tourism Group, Sathingpra District, Songkhla Province. This research purposed to upgrade and develop the quality and standardized herbal soap from the Palmyrah fruit of the Conservation Tourism Group, Sathingpra District, Songkhla Province, and also supported the marketing management of the Group. The research methodology was participatory actions which presented the results as follows; 1) From the development of the products, group had the potential to raise standards of products in terms of the quality, the process, the packaging, the marketing and the accounting. 2) The results from testing the Herbal Cosmetics products soap from Palmyrah fruit to test the effects of the Antimicrobial activity, the soap could anti-fungal. 3) From the development of processing and packaging focusing the community participation, and the local identity. The products could admit with community harmoniously and effectively